Upregulation of Neogenin-1 by a CREB1-BAF47 Complex in Vascular Endothelial Cells is Implicated in Atherogenesis - Li, Nan; Liu, Hong; Xue, Yujia; Chen, Junliang; Kong, Xiaocen; Zhang, Yuanyuan (Frontiers in Cell and Developmental Biology, 2022)
Atherosclerosis is generally considered a human pathology of chronic inflammation, to which endothelial dysfunction plays an important role. Here we investigated the role of neogenin 1 (Neo-1) in oxidized low-density lipoprotein (oxLDL) induced endothelial dysfunction focusing on its transcriptional regulation. We report that Neo-1 expression was upregulated by oxLDL in both immortalized vascular endothelial cells and primary aortic endothelial cells. Neo-1 knockdown attenuated whereas Neo-1 over-expression enhanced oxLDL-induced leukocyte adhesion to endothelial cells. Neo-1 regulated endothelial-leukocyte interaction by modulating nuclear factor kappa B (NF-κB) activity to alter the expression of adhesion molecules. Neo-1 blockade with a blocking antibody ameliorated atherogenesis in Apoe−/− mice fed a Western diet. Ingenuity pathway analysis combined with validation assays confirmed that cAMP response element binding protein 1 (CREB1) and Brg1-associated factor 47 (BAF47) mediated oxLDL induced Neo-1 upregulation. CREB1 interacted with BAF47 and recruited BAF47 to the proximal Neo-1 promoter leading to Neo-1 trans-activation. In conclusion, our data delineate a novel transcriptional mechanism underlying Neo-1 activation in vascular endothelial cells that might contribute to endothelial dysfunction and atherosclerosis.